Performance characterization and combination design optimization of fast-melting SBS/CR modified asphalt - Jinyao Li; Wenwu Zhang; Weiwei Lu; Songtao Lv; Haihui Duan; Jinping Wang (Case Studies in Construction Materials)
To broaden the application prospects of fast-melting styrene-butadiene-styrene modifiers (F-SBS) and meet diverse requirements, this study utilizes crumb rubber (CR) as a partial substitute for F-SBS to prepare fast-melting SBS/CR modified asphalt (F-SCMA). Firstly, rheological tests were conducted on fast-melting SBS modified asphalt (F-SBSMA) with varying dosages of F-SBS (3.0 %, 3.5 %, and 4.0 %). Subsequently, F-SBS was added to the neat asphalt in dosages of 3.0 %, 2.5 %, 2.0 %, 1.5 %, and 1.0 %. CR was then incorporated into the F-SCMA in corresponding dosages (2 %, 3 %, 4 %, 5 %, 6 %, 7 %, 8 %, 9 %, and 10 %) to form F-SCMA with different ratios of F-SBS and CR. The dosage of F-SCMA was further determined using performance grade (PG), Brookfield viscosity, linear amplitude sweep (LAS), softening point difference, and multiple stress creep and recovery (MSCR) tests. Finally, the microscopic mechanisms of F-SCMA were characterized using Fourier transform infrared spectroscopy (FTIR) and fluorescence microscopy (FM) tests. The results indicated that F-SBS significantly enhanced the rheological properties of neat asphalt. The modified asphalt containing 3.5 % F-SBS exhibited a PG of 76–28, which represents the most significant modification effect among the various dosages of F-SBSMA. In comparison, the F-SCMA with 2.5 % F-SBS and 6 % CR demonstrated higher high- and low-temperature continuous PG, better temperature stability, improved elasticity, and enhanced fatigue resistance than 3.5 % F-SBSMA. F-SCMA containing 3 % F-SBS and 4 % CR, as well as 1 % F-SBS and 8 % CR, exhibited superior high- and low-temperature properties, respectively. Furthermore, FTIR and FM tests revealed that F-SBS and CR were effectively incorporated into the asphalt through a physical mixing process, indicating compatibility between the two modifiers and the neat asphalt. This study establishes a theoretical framework for assessing the comprehensive performance of F-SCMA, expands the application prospects of F-SBS, and provides design concepts for the application of F-SCMA in environments with different requirements.